A sustainable food security approach: Controlled land application of sewage sludge recirculates nutrients to agricultural soils and enhances crop productivity. (23rd January 2020) - Eid, Ebrahem M.; Alamri, Saad A.M.; Shaltout, Kamal H.; Galal, Tarek M.; Ahmed, Mohamed T.; Brima, Eid I.; Sewelam, Nasser
Abstract: The food security in today's world is endangered by several threats, including accelerated increases in the world's population, depletion of the Earth's resources, exaggerated environmental pollution, and foreseen climatic changes. As a strategy to diminish these threats, the wise disposal of the huge amounts of sewage sludge (SS) to agricultural soils as a bio‐fertilizer represents a worthy practice for recirculating valuable nutrients to food chains via crop plants. The current study was designed to scientifically test the feasibility of SS application to agricultural soils without causing environmental or health threats. Different SS amendment doses of 0, 10, 20, 30, 40, and 50 g/kg were supplied for soil‐grown barley ( Hordeum vulgare L.) plants. Our results show that all of the SS amendment doses improved the postharvest soil properties and enhanced barley growth, with the best results obtained at the 40 g/kg dose. At this amendment dose, the organic matter (OM) content increased to 6.7% compared with 1.4% in control soil. Analysis of the postharvest soils showed that the concentrations of the investigated heavy metals (HMs) (Co, Cu, Mo, Ni, Zn, Cd, Cr, and Pb) were within the allowable limits for agricultural soils at all of the SS amendment doses, except for Co. All of the SS amendment rates enhanced barley growth and yield parameters, including shoot and root lengths and dry weights, spike weight and number of spikes per plant. Up to the 40 g/kg amendment dose, the concentrations of the investigated HMs in the harvested plant tissues were within safe limits, with most of the absorbed HMs persisting in roots. Taking these results together, the current study suggests that controlled application of SS to agricultural soils represents an eco‐friendly SS disposal procedure, which can recycle macro‐ and micronutrients to food chains and hence provide a promising approach for sustainable food security. Abstract : This study was designed to scientifically test the feasibility of sewage sludge (SS) application to agricultural soils as a practice for recirculating valuable nutrients to crop plants, without causing environmental or health threats. Our data provide evidence that the controlled application of SS to agricultural soils represents an eco‐friendly SS disposal procedure, which can recycle macro‐ and micronutrients to food chains and hence provide a promising approach for sustainable food security.